2011
DOI: 10.1258/jhsrp.2011.011050
|View full text |Cite
|
Sign up to set email alerts
|

Health technology assessment: Research trends and future priorities in Europe

Abstract: The research priorities identified are important for obtaining high quality and cost-effective health care in Europe. Managing the introduction, use and phasing out of technologies challenges health services throughout Europe, and these processes need to be improved to successfully manage future more general challenges. An ageing population and a diminishing workforce both require strong efforts to ensure effective and well-organized use of human resources and technologies. Furthermore, Europe needs to focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 57 publications
1
31
1
5
Order By: Relevance
“…Health technology assessment entities. Evidence used in HTA includes the safety, efficacy, effectiveness, cost, social, institutional, legal, and ethical implications of new technology adoption, although the precise use and methodology differs from agency to agency [112,113]. (Whereas LMIC are the focus of this paper, the working group also examined HTA processes in European countries.…”
Section: N a T I O N A L E F F O R T S T O S U P P O R T P R I O R I mentioning
confidence: 99%
“…Health technology assessment entities. Evidence used in HTA includes the safety, efficacy, effectiveness, cost, social, institutional, legal, and ethical implications of new technology adoption, although the precise use and methodology differs from agency to agency [112,113]. (Whereas LMIC are the focus of this paper, the working group also examined HTA processes in European countries.…”
Section: N a T I O N A L E F F O R T S T O S U P P O R T P R I O R I mentioning
confidence: 99%
“…Asimismo, se propone dotar de una mayor flexibilidad a los presupuestos, supeditada a la ejecución de actividades calificadas como eficientes [14]. Por otro lado, para promover la aceptación social de la ETS, se recomienda una mayor transparencia, así como la involucración de todos los agentes (industria, políticos, profesionales clínicos, pacientes y ciudadanos) en las distintas fases del proceso de evaluación [8,9,12,18,19,21]. Para solventar el problema de las barreras metodológicas encontradas se sugiere, en primer lugar, llevar a cabo una estandarización y unificación de la metodología utilizada para la realización de las ETS y, en segundo lugar, una homogeneización y explicitación de los criterios de priorización y evaluación de las tecnologías [14,18].…”
Section: Resultsunclassified
“…Para solventar el problema de las barreras metodológicas encontradas se sugiere, en primer lugar, llevar a cabo una estandarización y unificación de la metodología utilizada para la realización de las ETS y, en segundo lugar, una homogeneización y explicitación de los criterios de priorización y evaluación de las tecnologías [14,18]. Por lo que concierne al establecimiento de prioridades, algunos autores sugieren la implantación de programas de "horizon scanning" con el objetivo de proporcionar asesoramiento sobre el impacto potencial de tecnologías emergentes antes de que lleguen al mercado [21,22]. Adicionalmente, para favorecer la contextualización de las recomendaciones y su implementación en la práctica clínica habitual, se propone la incorporación en la evaluación de la información procedente de estudios de efectividad comparada (ensayos pragmáticos, registros y estudios observacionales) y adaptar las recomendaciones a las necesidades de los usuarios finales [2, 3, 9, 12].…”
Section: Resultsunclassified
“…6,[8][9][10][11][12][13] Second, prior reviews have found that rapid review products employ a range of strategies to reduce the time required to produce the final report. This includes different methods used to identify relevant literature, [14][15][16] different approaches to assessing quality, 6,10 and different levels of evidence synthesis.…”
Section: Introductionmentioning
confidence: 99%